Measurement of stapes footplate thickness in otosclerosis by ultra-high-resolution computed tomography. (1st November 2020) - Akazawa, Yukinori; Ganaha, Akira; Higa, Teruyuki; Kondo, Shunsuke; Oyakawa, Yoshiki; Hirakawa, Hitoshi; Suzuki, Mikio; Yamashiro, Tsuneo
Abstract: Background: Ultra-high-resolution computed tomography (U-HRCT) utilizes a 1024 × 1024 matrix with 0.25-mm section thickness, offering better spatial resolution than conventional multi-detector row CT to detect anatomic data for otologic surgery. Aims: We examined stapes footplate thickness using U-HRCT in relation to stapedotomy to predict the difficulty of the surgical procedure. Materials and methods: Subjects were 12 otosclerosis patients and 25 controls who underwent diagnostic U-HRCT. A profile curve (Hounsfield units) was used to measure stapes footplate thickness along a perpendicular line across the stapes footplate in a plane parallel to the lateral semicircular canal. Results: Footplate thickness was smaller at the midpoint than just before the anterior crus and just after the posterior crus. Interobserver variability was lowest at the midpoint, where foot plate thickness was significantly greater in the affected ear in otosclerosis patients compared with controls (0.60 ± 0.09 mm vs 0.46 ± 0.04 mm; p < .001). Otosclerosis patients were detected using U-HRCT with a high area under the curve. Difficulty in the stapes opening procedure correlated with stapes footplate thickness. Conclusions: Footplate thickness on U-HRCT correlated with temporal bone anatomy and corresponded to surgical difficulty. Significance: U-HRCT-derived anatomic data is useful for evaluating the stapes.